The Burial of Psusennes I and “The Bad Times” of P. Brooklyn 16.205 - Thijs, Ad (Zeitschrift für ägyptische Sprache und Altertumskunde, 2014)
This article deals with the last decade of the reign of Psusennes I in the light of the short chronology set out in earlier articles by the same author. It is argued that the burials of Psusennes I, HPA Menkheperre, HPA Nesubanebded, Khakheperre Pinuzem, the Devotee of Hathor Henttawy and Queen Nodjmet all took place within a very short period of time, called in P. Brooklyn 16.205 “the Bad Times”. Elements of the funeral equipment of these individuals are discussed and several severe problems with the traditional views on these burials are highlighted. The author further discusses the Report of Wenamun and presents an alternative identification for its Nesubanebded.